1991
DOI: 10.1113/jphysiol.1991.sp018743
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mild cold on the components of 24 hour thermogenesis in rats.

Abstract: SUMMARY1. The influence of two weeks' acclimation to either 28°C (thermal neutrality) or 21°C (mild cold) on 24 h heat production and motor activity has been investigated in male Wistar rats. Food intake was controlled and provided as a single meal of approximately 170 kJ per day. Mathematical modelling was used to relate metabolic rate to measured movement and time of day.2. For animals at thermal neutrality it was clear that metabolic rate increased during periods of substantial measured movement and returne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 36 publications
6
16
1
Order By: Relevance
“…Morrison [27] first demonstrated that SPA in rodents accounted for 25% of total energy expenditure, the magnitude of which was later confirmed by Brown et al [28] and Girardier et al [29]. These findings in rodents parallel data from human studies demonstrating the significant impact of SPA-induced energy expenditure on total energy expenditure [9, 16, 30].…”
Section: Physiological Significance Of Spa and Neat To Energy Balancesupporting
confidence: 75%
“…Morrison [27] first demonstrated that SPA in rodents accounted for 25% of total energy expenditure, the magnitude of which was later confirmed by Brown et al [28] and Girardier et al [29]. These findings in rodents parallel data from human studies demonstrating the significant impact of SPA-induced energy expenditure on total energy expenditure [9, 16, 30].…”
Section: Physiological Significance Of Spa and Neat To Energy Balancesupporting
confidence: 75%
“…It is well known that an ambient temperature of 21 8C represents a mild cold stress to an individually housed rat (Brown et al 1991). Indeed, total heat production over 24 h was w25% higher for rats at 21 than 28 8C and underlying thermogenesis was w20% higher for those in mild cold (Golozoubova et al 2004, Feldmann et al 2009.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that 'catch-up' growth of some organs or tissues was occurring between the second and fourth weeks of postnatal life, despite no change in feed intake between groups. A possible explanation for this effect is that CR lambs were altering their sleep-wake-activity cycles, which can act to conserve energy in cold-acclimated animals (Brown, Lavas & Dauncey, 1991), thereby increasing energy available for growth.…”
Section: Discussionmentioning
confidence: 99%